Risk Factors for Febrile Seizure Recurrence - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The relation between postulated risk factors and seizure recurrence after a first febrile seizure (FS) was assessed by reanalysis of pooled data from five centers and follow-up studies and reported from the Sophia Children's Hospital, Rotterdam, The Netherlands.